2019
DOI: 10.31744/einstein_journal/2019ao3434
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor-negative as a predictive factor for pathologic complete response to neoadjuvant therapy in breast cancer

Abstract: ObjectiveTo define a predictive factor for pathologic complete response, compare the oncologic outcomes associated with the degree of pathologic response after neoadjuvant chemotherapy, and to analyze pathologic complete response as a prognostic factor for overall survival and progression-free survival.MethodsA retrospective study of patients admitted to Hospital Estadual Mário Covas and Hospital Anchieta from 2008 to 2012, with locally advanced breast cancer. Hormone receptor status, HER2 status, histologic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The sensitivity analysis considered variations in the effectiveness of different sub-groups, changing the clinical staging and positive/negative ER and PR in each tested scenario. Patients with negative HR had better overall clinical results compared with patients with positive HR, which is in line with available literature [30]. The clinical staging II with negative HR resulted in an higher ICER versus clinical staging II with positive HR.…”
Section: Discussionsupporting
confidence: 88%
“…The sensitivity analysis considered variations in the effectiveness of different sub-groups, changing the clinical staging and positive/negative ER and PR in each tested scenario. Patients with negative HR had better overall clinical results compared with patients with positive HR, which is in line with available literature [30]. The clinical staging II with negative HR resulted in an higher ICER versus clinical staging II with positive HR.…”
Section: Discussionsupporting
confidence: 88%
“…The frequency of pCR was also higher in patients with HR-negative cancer, which is in line with previous studies. [ 28 30 ] The dual-blockade group had a greater proportion of conservative surgery and a lower rate of axillary clearance, as expected.…”
Section: Discussionsupporting
confidence: 66%
“…In the study by Silva et al of 243 patients, the presence of negative hormone receptors was found to be a predictive factor of pCR and associated with shorter OS and DFS. pCR was found to be associated with longer DFS and OS 17 . In several studies where pCR was achieved after NAC, it has been shown that the risk of death decreases and OS increases 9,15,17,18 .…”
Section: Discussionmentioning
confidence: 91%